Pengaruh Pemberian Remunerasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Sekretariat Daerah Kantor Bupati Kabupaten Karimun - Illif Rizki Andreyani Syihab; Agus Hendrayady; Jamhur Poti (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this study was to determine and analyze the effect of remuneration and work motivation on employee performance, to determine and analyze the provision of remuneration on employee performance, to determine and analyze the provision of remuneration and work motivation together on employee performance at the Karimun Regency Regent's office. The approach used in this research is an associative approach. An associative approach is an approach using two or more variables to determine the relationship or influence between one variable and another. The population in this study amounted to 155 people with a sample in this study of 61 people. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses Measurement Model Analysis (Outer Models), Structural Model (inner model) and Hypothesis Test. Data processing in this study used the SmartsPLS 4.0 software program. From the results of the study it can be concluded that the results of the first hypothesis test show that the relationship between the variable of remuneration and employee performance has a correlation value of 0.465. The second hypothesis test results show that the relationship between work motivation variables and employee performance has a correlation value of 0.366. Based on the calculation results, it shows that remuneration and work motivation have a fairly positive effect on employee performance. This is evidenced by the R Square value of 0.586. This shows that the provision of remuneration and work motivation on employee performance still needs to be improved so that the performance of employees is getting better.